FSK Demodulation and Bit String Extraction: A Python-Centric Approach in SDR Systems - Sanchez, Jimi (2024)
Frequency Shift Keying (FSK) modulation is widely utilized in various communication systems for data transmission due to its simplicity and robustness. In this paper, we present a Python-centric approach for demodulating FSK signals and extracting bit strings in Software Defined Radio (SDR) systems. Leveraging the flexibility and power of Python programming language along with SDR platforms, we explore the intricacies of FSK demodulation techniques and efficient bit string extraction methods. Our approach focuses on real-time processing capabilities, enabling rapid decoding of FSK signals with minimal latency. We discuss the implementation details, performance considerations, and optimization strategies, highlighting the advantages and challenges of utilizing Python in SDR applications. Furthermore, we demonstrate the effectiveness of our approach through experimental results and comparisons with existing methods. This paper serves as a comprehensive guide for researchers and practitioners interested in implementing FSK demodulation and bit string extraction algorithms using Python within the context of SDR systems.